Use of the modified progenic apparatus in the previous cross-bite interception (Research, Society and Development, 2020)
An interceptive orthodontia allows the correction of the anterior crossbite early, in order to promote or harmonious growth of the osseous bases. There are alternatives for the treatment of the cross bite prior to the use of the removed devices as a modified progeny. The objective of this work is to carry out or the report of a clinical case of anterior crossbite treated with this approach. Patient with nine years of age, feminine sex and in the phase of dentição mista. No clinical examination observed a diminution of the zygomatic projection and maxillary deficiency. A cephalometric analysis verified a negative maxillo-mandibular relationship, due to the tendency of vertical growth and lower incisors to be positioned. After making the dress, you are ready to install and stay after seven days, using a protocol for maintenance once a week for three weeks. Or the modified progeny has been shown to be effective without treatment of the anterior crossbite in a three-week period, enabling or derailing the maxilla for a more harmonious growth of bone bases. Or use of the fast and effective modified progeny device without dentoalveolar anterior crossbite interceptor treatment. It will be necessary to preserve the case, supervising or developing the occlusion and growth of the bone bases.